Image and graphics. 8th International Conference, ICIG 2015, Tianjin, China, August 13-16, 2015, Proceedings /: 8th International Conference, ICIG 2015, Tianjin, China, August 13-16, 2015, Proceedings. Part II : (2015) - Unknown
No abstract available